Analisis Al-Wujūh wa al-Naẓā’ir terhadap Keragaman Makna Lafaz Hudā dalam Al-Qur’an - Misdah, Misdah; Miswar, Andi; Ilyas, Hamkah (EL-MAQRA', 2026)
This study aims to analyze the variation of meanings and semantic relations of the hudā in the Qur’an through the al-wujūh wa al-naẓā’ir approach. The research employs a qualitative library research method using Qur’anic verses containing derivations of the root h-d-y as the primary data source. The data were analyzed using a contextual semantic approach by examining syntactic structures, verse contexts, subjects giving guidance, and objects receiving guidance. The findings reveal that hudā carries various meanings, including the Qur’an, faith, Islam, divine guidance (tawfīq), and prophets or messengers as guides for humanity. Furthermore, hudā demonstrates semantic relations with terms such as īmān, taqwā, ṣirāṭ, and ḍalāl, forming a semantic field within the Qur’anic conceptual system. These findings indicate that the concept of guidance in the Qur’an is relational, dynamic, and contextual, demonstrating the continued relevance of the al-wujūh wa al-naẓā’ir approach in contemporary Qur’anic semantic studies.